Evidence-based nursing practice in intrapartum period [İntrapartum dönemde kanita dayali hemşirelik uygulamalari] - (:unkn) unknown (My University, 2006)
Evidence based practices, within the last years, have become common in healthcare settings. Integrating this concept to nursing will enhance the quality of nursing care. The purpose of this article is to contribute to the improvement of obstetrics and gynecology by studying present evidence and current practices during the intrapartum period.